1995
DOI: 10.1136/hrt.74.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Atrial electromechanical sequence in normal subjects and patients with DDD pacemakers.

Abstract: Right atrial appendage pacing disturbs the normal coordinate sequence of right atrial mechanical activity and leads to a striking and variable increase in intra-atrial conduction time as well as in interatrial conduction time. Left atrial contraction remains synchronous although the timing of the start of its contraction was delayed. These values can be determined in individual patients to allow optimal setting of DDD pacemakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 18 publications
4
36
1
1
Order By: Relevance
“…These are PWD that is an electrocardiographic parameter and AEMD and ACT that are measured by TDI study (13)(14)(15)(16)(17) . In addition, in various contributing factors to develop AF such as obstructive sleep apnoea, diastolic dysfunction, dilated cardiomyopathy and hypertension the prolongation of AEMD during sinus rhythm has been reported (12,(18)(19)(20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…These are PWD that is an electrocardiographic parameter and AEMD and ACT that are measured by TDI study (13)(14)(15)(16)(17) . In addition, in various contributing factors to develop AF such as obstructive sleep apnoea, diastolic dysfunction, dilated cardiomyopathy and hypertension the prolongation of AEMD during sinus rhythm has been reported (12,(18)(19)(20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are some echocardiographic methods to measure interatrial conduction times by the evaluation www.cardiologyjournal.org of cardiac electromechanical events. The time interval between the electrocardiographic P wave and the atrial contraction detected by M-mode or Doppler echocardiography is defined as atrial electromechanical delay [9][10][11]. Atrial mechanical activity can be detected from different atrial regions by tissue Doppler echocardiography with high temporal resolution [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the absolute value of the global interatrial delay did not differ between the groups. Physiologically, RA precedes LA contraction 12,[15][16][17] and according to Barletta et al who have studied atrial contraction sequence in 66 healthy subjects, the mean interatrial delay amounts to 17.7±2.8 ms (−40-60 ms); 15 however, occasionally a reversed atrial contraction sequence can be observed. So far, 2 groups of investigators have examined the atrial contraction sequence during MAP, and in all their patients 1 of the atrial leads was placed in the RAA.…”
Section: Discussionmentioning
confidence: 99%